Cemento-ossifying fibroma-a rare case - Sarwar H; Jindal M; Ahmad S (Wolters Kluwer Medknow Publications, 2008)
The concept of ′fibro-osseous lesions′ of bone has evolved over the last several decades and now includes two major entities: fibrous dysplasia and ossifying fibroma, as well as the other less common lesions such as florid osseous dysplasia, periapical dysplasia, focal sclerosing osteomyelitis, proliferative periostitis of garrie, and ostitis deformans. The cemento-ossifying fibroma is a central neoplasm of bone as well as periodontium which has caused considerable controversy because of confusion regarding terminology and the criteria for its diagnosis. The cemento-ossifying fibroma is odontogenic in origin, whereas ossifying fibroma is of bony origin. This article reports a rare case of an 11-year-old male who came to us with the history of swelling in the maxillary anterior region causing difficulty in closing of mouth as well as in mastication.